1987
DOI: 10.1063/1.527681
|View full text |Cite
|
Sign up to set email alerts
|

Quantization: Towards a comparison between methods

Abstract: In this paper it is shown that the procedure of geometric quantiztion applied to Kähler manifolds gives the following result: the Hilbert space ℋ consists, roughly speaking, of holomorphic functions on the phase space M and to each classical observable f (i.e., a real function on M) is associated an operator f on ℋ as follows: first multiply by f+ 1/4 ℏΔdRf (ΔdR being the Laplace–de Rham operator on the Kähler manifold M) and then take the holomorphic part [see G. M. Tuynman, J. Math. Phys. 27, 573 (1987)]. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…in [16] and more recently in [17]. Generalized Berezin and Berezin-Toeplitz quantizations were defined and analyzed in [10] and include interesting new possibilities, such as Berezin-Bergman quantization.…”
Section: Jhep05(2009)055mentioning
confidence: 99%
See 2 more Smart Citations
“…in [16] and more recently in [17]. Generalized Berezin and Berezin-Toeplitz quantizations were defined and analyzed in [10] and include interesting new possibilities, such as Berezin-Bergman quantization.…”
Section: Jhep05(2009)055mentioning
confidence: 99%
“…Such an operator has the block diagonal structure A = A + ⊕ A − (with A ± ∈ GL(E ± )) where A ± are ( , ) ± -Hermitian and A + is positive definite. The supercoherent states with respect to the new product ( , ) ′ , which in turn induces the pairing (( , )) ′ x , are given by: 16) while the new supercoherent projectors take the form:…”
Section: Changing the Superscalar Product In Generalized Berezin Quanmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (5.2) is related to a formula due to Tuynman [13]. Namely, for any smooth function f ∈ C ∞ (M),…”
Section: Geometric Quantizationmentioning
confidence: 99%
“…This link between geometric and Berezin quantization was discovered by Tuynman [242] [243], who showed that on a compact Kähler manifold (as well as in some other situations) the operators Q f of the geometric quantization coincide with the Toeplitz operators T f +h∆f , where ∆ is the Laplace-Beltrami operator. Later on this connection was examined in detail in a series of papers by Cahen [55] and Cahen, Gutt and Rawnsley [56] (parts I and II of [56] deal with compact manifolds, part III with the unit disc, and part IV with homogeneous spaces).…”
mentioning
confidence: 99%